2011
DOI: 10.1371/journal.pone.0022230
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Viral mRNA without Active eIF2: The Case of Picornaviruses

Abstract: Previous work by several laboratories has established that translation of picornavirus RNA requires active eIF2α for translation in cell free systems or after transfection in culture cells. Strikingly, we have found that encephalomyocarditis virus protein synthesis at late infection times is resistant to inhibitors that induce the phosphorylation of eIF2α whereas translation of encephalomyocarditis virus early during infection is blocked upon inactivation of eIF2α by phosphorylation induced by arsenite. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 57 publications
4
32
0
Order By: Relevance
“…The resistance of the mRNA translation to the arsenite stress is regarded as a specific marker for relaxed eIF2-dependence27313233. Arsenite at concentrations of 20 μM or more inhibited translation of the Actin-Rluc mRNA almost completely, in accordance with our previous data2731.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The resistance of the mRNA translation to the arsenite stress is regarded as a specific marker for relaxed eIF2-dependence27313233. Arsenite at concentrations of 20 μM or more inhibited translation of the Actin-Rluc mRNA almost completely, in accordance with our previous data2731.…”
Section: Resultssupporting
confidence: 88%
“…2). Another test that could be used to assess a relaxed eIF2 dependency in vivo is translation resistance to unfolded protein stress caused by dithiotreithol273133. Again, the leaderless mRNA translation showed pronounced resistance to this kind of stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a positive control for phosphorylated eIF2␣, avian cells were treated with dithiothreitol (DTT), a reducing agent that activates the endoplasmic reticulum kinase PERK to induce eIF2␣ phosphorylation and protein synthesis inhibition in mammalian cells (39,40). The results shown in lanes 9 of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One class of these mRNAs, such as those encoding activating transcription factor 4 (ATF4), contain upstream open reading frames (uORFs) in their 5= untranslated regions and require these uORFs and eIF2␣ phosphorylation for efficient translation of the main ORF (15,(82)(83)(84). Another class of transcripts contain internal ribosome entry site (IRES) or downstream loop (DLP) structures, which allow them to recruit Met-tRNA i met in the absence of eIF2 (40,82,(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95). On the other hand, phosphorylation of eIF2␣ has been reported to occur in cells infected with rotavirus, a member of the Reoviridae family; under these restrictive conditions, the synthesis of most cellular proteins is inhibited while viral transcripts are efficiently translated (96), suggesting that translation of rotavirus transcripts is quite resistant to eIF2␣ phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Another translation initiation factor eIF4GII as well as the polyA binding protein (PABP), a protein facilitating the formation of a closed translation initiation loop by interaction of the 5' and 3' ends of the mRNA, has been reported to be cleaved by picornaviral 2A (Gradi, et al, 1998, Joachims, et al, 1999. All these cleavages often correspond with a translational shift to IRES-dependent translation Welnowska, et al, 2011, rendering the eIFs incapable of performing cap-dependent translation. Another group also showed that the shift in translation seen during the later phase of poliovirus infection is not entirely due to phosphorylation (inactivation) of eIF2 (see discussion in later session), but may also depend upon protease 3C activation and cleavage of another translation initiation factor, eIF5B, to a C-terminal truncated version thought to replace eIF2 during translation (White, et al, 2011).…”
Section: Cleavage Of Translation Initiation Factors By Viral Proteasesmentioning
confidence: 99%